Acrodermatitis Continua of Hallopeau with Bone Resorption in an 8-Year-Old Patient: A Case Report - May Alorainy; Mohammed Alshaya; Ammar Al-Rikabi; Mohammed Ayesh; Fahad Alsaif (Karger Publishers, 2017)
Acrodermatitis continua of Hallopeau (ACH) is an uncommon inflammatory disease manifesting as sterile pustular eruption of the fingers and toes. The disease is of a chronic relapsing nature and is often refractory to treatment. With longstanding disease, osteitis with consequent bone resorption of the underlying phalanges can occur, leading to disability. While the incidence of ACH is rare in children, complications like osteolysis have not been reported previously in this age group. In this paper, we report the case of an 8-year-old boy with severe ACH complicated by bone resorption.